Analysis of pressure at transition zone of valve plate of radial piston pump. (1st September 2022) - Kumar, Lokesh; Mandal, Nimai Pada
Abstract: In present studies focuses on the characteristics of flow-pressure of piston cylinder barrel and silencing groove chambers near the transition zone of valve plate of a fixed displacement radial piston pump. The designing of silencing groove of valve plate of the pump is carried out with appropriate geometrical configuration, compute the orifice area of piston kidney over the silencing grooves and manifolds, the interaction area make a key role in fluid flow interaction. The pressure and flow of pump is analyzed in consideration the silencing groove as separate control volume from manifold, each silencing groove chamber is connected to the both end of the manifold chamber, the shape of the silencing groove is an asymmetric tetrahedron. The radial piston pump is modelled in simulation with consideration of five pump pistons barrel, analyses the pressures near at transition zone with different bridge angle. The flows interaction of pump piston cylinder barrel with silencing groove chamber and manifold chamber are also carried out. The overall pump volumetric efficiency, flow and pressure fluctuation of radial piston pump are analyzed to optimize the pump.